Study of adsorptive removal efficiency of iron ions from the solutions within different acidity - Bolshanina, S. B.; Ivchenko, V. D.; Ablieieva, I. Yu. (Visnyk of Vinnytsia Politechnical Institute, 2014)
Adsorption of ions Fe3+ and Fe2+ on clay minerals of Sumy region has been studied in order to evaluate efficiency of lo-cal clay minerals in environmental technologies. It has been shown that adsorption processes of ions Fe3+ and Fe2+ are different both in terms of adsorption and of the mechanism of the process. Fe2+ ions are adsorbed to greater extent than Fe3+ ions. Chemical sorption followed by physical vapor deposition is probable for Fe2+ ions, and conventional ion exchange or physical adsorption is probable for Fe3+ ions. It has been found that adsorption of Fe3+ ions can be effective only in solu-tions having not less than 2 pH, which corresponds to Fe3+ ion content of not more than 0.01-0.02 mol-eq / l. The use of clay as adsorbent for removing iron ions from aqueous solutions is useful and effective in the purification process, in conjunction with other reactant and physical and mechanical methods.